Genome-wide gene expression analysis reveals novel insights into the response to nitrite stress in gills of Branchiostoma belcheri. (March 2019) - Zhang, Qi-Lin; Zhang, Guan-Ling; Xiong, Yan; Li, Hong-Wei; Guo, Jun; Wang, Feng; Deng, Xian-Yu; Chen, Jun-Yuan; Wang, Yu-Jun; Lin, Lian-Bing
Abstract: Amphioxus has been widely used as a model for the comparative immunology of vertebrates. Studies have reported that gene expression changes in the amphioxus gill in response to biotic stress, such as microbial and their mimic challenge, but little is known about how gene expression is affected by abiotic stress in the marine environment, such as nitrite. A lack of information regarding gene expression response to abiotic stress hinders a comprehensive understanding of gill defense response in amphioxus. Here, RNA sequencing was used to carry out gene expression profiling analyses of Branchiostoma belcheri gills under nitrite stress. Six libraries were created for the control and treatment groups, including three biological replicates. In total, 2416 differently expressed genes (DEGs) were detected in response to nitrite stress, of which 1522 DEGs were up-regulated in the treatment group in comparison to the control, while the remaining 894 DEGs were down-regulated genes. Functional enrichment revealed that these DEGs are primarily involved in disease, innate immunity, xenobiotic biodegradation and metabolism, and biomolecular processes and apoptosis. We screened 11 key nitrite-responsive DEGs to detect their expression responses to nitrite stress at different time points, and validate the sequencing data using real time quantitative PCR. The results indicated that the expression of gene encoding CYP3A, POD, CASPR1, GST, MAO, DDH, and XDH/XO were induced, while those encoding MRC, GT, DNASE1L, and RIPK5 were reduced, to participate in the anti-nitrite response. This study provides a useful resource for research of molecular toxicology in amphioxus under environmental stress. Highlights: Gene expression profiling was analyzed in Branchiostoma belcheri gills between control and nitrite-treated groups. 2, 416 genes presented expression response to nitrite stress. The analysis of qRT-PCR confirmed the accuracy of expression profiling results. We screened 11 key nitrite-responsive DEGs.